PENINGKATAN KAPASITAS POKDARWIS MELALUI PELATIHAN ADMINISTRASI KEUANGAN DI SAKRA BARAT KABUPATEN LOMBOK TIMUR - Hanani, Tri; Rizki, Novia; Agustiningsih, Wulandari; Hartini, Intan Juwita (Jurnal Abdimas Sangkabira, 2024)
The tourism sector is one of Indonesia's leading sectors. Pokdarwis is a community group that voluntarily cares about managing and improving regional tourism. Pokdarwis often receive funds for activities that must be managed and accounted for properly, including Pokdarwis of Rensing Sakra Barat Village. This community service activity aims to increase the capacity of Human Resources of Pokdarwis Sakra Barat, East Lombok Regency, through financial administration training. With this training, Pokdarwis is expected to be able to carry out complete and structured financial administration so that all finances are recorded and reported correctly. The activity was carried out for one day, on May 21, 2024, attended by the management and members of Pokdarwis at the culinary market, a local tourist spot they currently manage. The community service team presented material and examples of financial administration by linking the actual situation according to what was conveyed by Pokdarwis members. From the evaluation results, the management and members of Pokdarwis stated that the activity provided sufficient understanding and expressed satisfaction with the activity facilities.